A general design procedure for failure mechanism control of reinforced concrete frames. (1st July 2016) - Montuori, Rosario; Muscati, Roberta
Highlights: New advances for designing RC-MRF failing in a global mode are presented. Beams present different reinforcement at the top and bottom part of the section and at the ends. The application of the TPMC to the design of a multi-storey frame is presented. Both push-over analyses and non-linear dynamic analyses have been made. Abstract: In this paper new advances for designing moment resisting concrete frames, failing in a global mode (TPMC: Theory of Plastic Mechanism Control), are presented. The TPMC theory has been developed in the nineties with reference to moment-resisting frames (MRFs) and progressively extended to several steel structural typologies commonly adopted as seismic-resistant structural systems. The proposed procedure is based on the application of the kinematic theorem of the plastic collapse through the evaluation of the sum of the plastic moments of the columns required, at each storey, to prevent undesired failure modes such as soft-storey mechanism. The second-order effects, due to vertical loads, can play an important role in the seismic design of reinforced concrete (RC) frames. For this reason, they can be taken into account in the proposed approach through the equilibrium of the considered collapse mechanism. Significant improvements proposed by this approach include, among others, the possibility to account for different amount of reinforcement, not only at the top and bottom of the beam section, but also at the beam ends (left and right). A practical application of the TPMC process for the design of a multi-storey RC frame is presented with push-over and non-linear dynamic analyses that investigate the actual collapse mechanism of the designed structure. All the obtained results confirm the capability of the design procedure to achieve a collapse mechanism of global type.